Interpersonal stranger violence and American Muslims: an exploratory study of lived experiences and coping strategies. Issue 1 (1st January 2019) - Agrawal, Priyanka; Yusuf, Yousra; Pasha, Omrana; Ali, Shahmir H.; Ziad, Homayra; Hyder, Adnan A.
ABSTRACT: Hate crimes in the United States have drastically increased since 2015, particularly for the American Muslim population. There was a 17% hike in hate crimes against American Muslims in 2017 compared with the previous year. The objectives of the study were to document the experiences of interpersonal stranger violence, coping strategies and recommendations by American Muslims. We applied qualitative research methods to conduct seven focus group discussions with 37 participants in the Maryland area, throughout 2017. There were reports of verbal abuse, discrimination (in schools, workplace, college campuses, airports, Visa offices), bullying and microaggression. Individuals were torn between the public anxieties of being Muslim and their private attachment to their religious identity. Despite reports of fear and uncertainty, individuals applied caution, positive religious coping, and encouraged family and community engagement to gain and provide support to each other. This study illustrates the consequences that the 2016 US presidential election and Islamophobic rhetoric had on American Muslims. Further research will elucidate the long-term impact on health outcomes of these behaviors.